Von Neumann Algebra Preduals Satisfy the Linear Biholomorphic Property - Peralta, Antonio M.; Stachó, László L. (MATHEMATICA SCANDINAVICA, 2016)
We prove that for every $JBW^*$-triple $E$ of rank $>1$, the symmetric part of its predual reduces to zero. Consequently, the predual of every infinite dimensional von Neumann algebra $A$ satisfies the linear biholomorphic property, that is, the symmetric part of $A_*$ is zero.